2019
DOI: 10.3390/su11113152
|View full text |Cite
|
Sign up to set email alerts
|

Analyst Following, Group Affiliation, and Labor Investment Efficiency: Evidence from Korea

Abstract: This paper studies how analysts' group affiliation affects firms' labor investment efficiency. Using a 2001-2017 sample of Korean public companies, we find that labor investment efficiency increases when there are more unaffiliated analysts following business group (chaebol) firms. Our regression results also suggest that an increase in labor investment efficiency is attributed to a reduction in firms' over-firing problem. However, affiliated analysts are not found to influence firms' labor investment efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Therefore, using regression residuals to measure investment inefficiency is accepted by most scholars. For example, Mo and Lee [45] used the deviation (represented by residuals) between the actual number of employees and the expected number of employees to represent the low efficiency of labor investment. Similarly, Oh et al [46] used the residual measurement method to construct investment inefficiency.…”
Section: Dependent Variable: Investment Inefficiencymentioning
confidence: 99%
“…Therefore, using regression residuals to measure investment inefficiency is accepted by most scholars. For example, Mo and Lee [45] used the deviation (represented by residuals) between the actual number of employees and the expected number of employees to represent the low efficiency of labor investment. Similarly, Oh et al [46] used the residual measurement method to construct investment inefficiency.…”
Section: Dependent Variable: Investment Inefficiencymentioning
confidence: 99%
“…From an external supervision perspective, analysts can supervise and give advice for managers' decisions. Therefore, more analyst tracking and higher accuracy of the analysts' predictions can enhance labor investment efficiency [17]. Internal governance can also influence labor investment efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ghaly et al (2020) [15] claim that institutional investors tend to supervise the decision-making process of the management and are often related to efficient labor investment. Scholars also find that analyst following, macropolicies, and CEO traits are the influencing factors of labor investment efficiency [16][17][18]. However, the existing research is still limited, and the relationship between CSR and labor investment efficiency is not generally known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mo and Lee (2019) [19] reported that an increase in labor investment efficiency is attributed to a reduction in a firm's over-firing problem. They document that the positive influence of unaffiliated analysts on labor investment efficiency holds when firms have high cash holdings.…”
Section: Labor Investment Efficiencymentioning
confidence: 99%